Policy Evaluation of Livable Houses Programs in Gorontalo City - Karim Lasulika; Muh. Firyal Akbar; Ramlah Alkatiri (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study aims to obtain an overview of the Policy Evaluation of Livable Houses Programs in Gorontalo City (Period 2016-2018). The research method uses a qualitative approach with descriptive research type. Data collection techniques are done through interviews with a number of informants and observations and recording secondary data related to research problems. The results of the study concluded that the evaluation of suitable program programs for habitation has not been effective, this is seen from the obstacles encountered in the distribution / construction of livable houses that must be in accordance with the stated objectives. Seen from the indicator of the equal distribution of programs that have been conducted unevenly. Accuracy in implementing policies has been done well but not yet optimal, this is because the accuracy in terms of policies is still lacking on the desired target, in this case the recipients of inappropriate housing programs are not appropriate.